Networking Effects on Supply Chain Performance: An Agent-Based Modeling Approach - Majumder, Madhumita Guha; Lokhande, Madhavi (International Journal of Economics, Business and Management Studies, 2019)
The objective of this article is to establish the fact that networking among supply chain agents enhances the performance of the system. The study has adopted an agent-based architecture for analyzing the networking effect of supply chain on an agricultural supply chain platform from an emerging economy. While carrying the products from a farmer to an urban customer, each downstream agent of an agricultural supply chain incurs additional transaction cost, and as a result, the price that the final customer pays becomes much higher than the farmers’ original selling price. Clearly, middle agents of supply chain consume a large chunk of profit which otherwise could have benefitted the farmer, the actual producers of the products. It is in this context this study shows that if farmers are networked on a blackboard architecture and the other intermediary agents including traders, commission agents, wholesalers, and retailers are also networked, then each agent becomes knowledgeable about others’ pricing strategies, both within and across the agent groups. This essentially reduces the transaction cost of the agents and thereby enhances the efficiency of the entire system. The study builds up an agent-based network structure and then simulates the effect of it. It finds that if both farmer agents and other intermediary agents are non-networked, then the efficiency of the system is only 29%, whereas if all agents are networked, then the efficiency rises to 92.43%. The research benefits the unorganized sector to gain rationality in income distribution in an underdeveloped society.